DAMPAK PENGGUNAAN E-SYSTEM PERPAJAKAN, SOSIALISASI PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WPOP DI KPP PRATAMA SURABAYA RUNGKUT - Ismawati, Jumrotul; Maqsudi, Achmad (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTTax Office Service Pratama Surabaya Rungkut, located at Jalan Jagir Wonokromo 104 Surabaya, is a fraction of the Tax Office Service Surabaya Wonocolo, which is charge of carrying out counseling, services and supervision of taxpayers in the taxation sector based on the applicable law. The purpose of this research is to determine the significant effects of taxation e-system, taxation socialization and taxation sanction on the compliance of personal taxpayers registered at Tax Office Service Pratama Surabaya Rungkut. Respondents were taken from all personal Taxpayers registered at KPP Pratama Surabaya Rungkut with a total of 110 people. This study uses quantitative research methods with the results of causal relationships, so that samples and hypotheses are used in this method. The analysis technique used is multiple linear analysis to test the hypothesis. Classic assumption tests used include, Multicollinearity Test, Heteroscedasticity Test, Normality Test, Autocorrelation Test and Linearity Test. All indicators used in this study are valid (correlation coefficient> 0.1918 with a significance level <0.05) and reliable (Cronbach's Alpha coefficient value> 0.60). From the results of the classic assumption test shows that this study has met the requirements, namely: 1.) Regression models free from multicollinearity; 2.) Free from the assumption of heteroscedasticity; 3.) Regression models are normally distributed; 4.) There is no autocorrelation; 5.) Both variables have a linear relation. From the results of data analysis concluded that, the impact of taxation e-system did not significant effect on the level of personal Taxpayers compliance at Tax Office Service Pratama Surabaya Rungkut, with a significance value of 0,229. While taxation socialization and taxation sanctions give a significant influence on the level of personal Taxpayers compliance at Tax Office Service Pratama Surabaya Rungkut, with a significance value of 0.029 and 0,000. The application of taxation e-system, taxation socialization and taxation sanctions simultaneously (together) give a significant influence on the level of personal Taxpayers compliance at Tax Office Service Pratama Surabaya Rungkut, evidenced by the results of simultaneous hypothesis testing (Test F) showing a significance value of 0,000.Keywords : Taxation e-system, taxation socialization, taxation sanction, personal taxpayers compliance